2018
DOI: 10.5194/acp-18-3173-2018
|View full text |Cite
|
Sign up to set email alerts
|

Increasing persistent haze in Beijing: potential impacts of weakening East Asian winter monsoons associated with northwestern Pacific sea surface temperature trends

Abstract: Abstract. Over the past decades, Beijing, the capital city of China, has encountered increasingly frequent persistent haze events (PHE). While the increased pollutant emissions are considered as the most important reason, changes in regional atmospheric circulations associated with large-scale climate warming also play a role. In this study, we find a significant positive trend of PHE in Beijing for the winters from 1980 to 2016 based on updated daily observations. This trend is closely related to an increasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 45 publications
3
65
0
Order By: Relevance
“…They also found that CESM may underestimate the recent decreases in Arctic sea ice and increases in Eurasian snow, meaning our results may underestimate the influence of climate change on the PPI distribution and its extremes (Zou et al, ). While we cannot conclude that anthropogenic warming has affected historical change in the WMI, Pei et al () hypothesized that positive SST anomalies in the northwest Pacific create anomalously high‐pressure systems off the eastern coast of China, which produce anomalous southerly winds and weaken the East Asian winter monsoon.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…They also found that CESM may underestimate the recent decreases in Arctic sea ice and increases in Eurasian snow, meaning our results may underestimate the influence of climate change on the PPI distribution and its extremes (Zou et al, ). While we cannot conclude that anthropogenic warming has affected historical change in the WMI, Pei et al () hypothesized that positive SST anomalies in the northwest Pacific create anomalously high‐pressure systems off the eastern coast of China, which produce anomalous southerly winds and weaken the East Asian winter monsoon.…”
Section: Discussionmentioning
confidence: 77%
“… Western Monsoon Index (WMI). We define an index of the East Asian winter monsoon following the approach of Pei et al (). The weakness of the monsoon is defined as the area‐averaged meridional wind anomaly at 850 hPa over 105–125 °E and 30–50 °N (Figure f).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on this topic have identified several key meteorological factors associated with the development of severe haze events, including weak surface winds (which reduce horizontal dispersion of urban aerosols; Wang et al, ; Zhang et al, ), a shallower and more stable atmospheric boundary layer (which inhibits vertical ventilation; Jeong & Park, ; Wang et al, ; Zhao et al, ), and enhanced relative humidity (RH; which intensifies secondary aerosol formation and hygroscopic growth; Quan et al, ; Sun et al, ; Wang et al, ). At larger scales, a weakened East Asian trough and a weak Siberian high may not only suppress vertical mixing and reduce boundary layer height (Pei et al, ; Zhang et al, ) but also reduce cold surges from high latitudes (e.g., Huang et al, ). Associated anomalous southerlies in the lower troposphere have been found to increase humidity and air temperature in North China, contributing to the formation and maintenance of severe haze (Chen & Wang, ; Yin et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the severe haze that developed in the Beijing‐Tianjin‐Hebei area during January 2013 (monthly mean PM 2.5 concentrations of ∼ 145 μg/m 3 ) has been attributed in part to a period of anomalously weak EAWM and SH (Wang et al, ; Zhang et al, ). Meteorological conditions during winter have grown increasingly favorable for the development of haze in eastern China since the mid‐1980s (Jeong & Park, ; Pei et al, ), coincident with a prolonged weakening of the EAWM (Huang et al, ; Lee et al, ), and reduced autumn Arctic sea ice has been dynamically linked to reduced ventilation of low‐level air over eastern China (Wang et al, ; Zou et al, ). Given these relationships, the frequency of haze formation in China is projected to increase under climate change (Cai et al, ; Hori & Ueda, ).…”
Section: Introductionmentioning
confidence: 99%